On the specificity and effects on transcription of P-element insertions at the yellow locus of Drosophila melanogaster. - Howes, G (1988)
Fourteen P-element insertion mutants at the yellow (y) gene of D. melanogaster have been analysed by restriction mapping and DNA sequencing. The distribution of the insertion sites is nonrandom, with a preferred target site in the 5'-transcribed but non-translated leader of the gene. Transcription analysis indicates that P-elements inserted into the transcribed region of y can terminate y transcription. While the great majority of the P-element insertions into the preferred target site abolish y activity, this loss of activity is not due to disruption of the insertion site since imprecise excision events which do not restore the wild type sequence at the insertion site can restore y function. We further demonstrate that a mutant caused by a 221bp P-element insertion into the 5' transcribed but non-translated region, which show partial y activity, produces a larger mutant transcript consistent with it being a product of transcriptional readthrough. We present results which suggest that imprecise excision events which restore (or partially restore) y activity can occur by deleting P-element internal sequences which normally act to terminate y transcription.